Design Systems and Component Packages as an Interface for Accessibility - Diniz, Sofia; Gama, Kiev (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3566, 2024)
A design system is a collection of interrelated patterns and shared practices, systematically organized to fulfill the objectives of digital products. This research aims to understand how Design Systems can influence software developers in implementing accessibility guidelines. For this purpose, leading design systems were analyzed for their coverage of accessibility, and a component package seamlessly integrating accessibility concerns was created and tested by software developers. Results indicated that an accessible Design System can positively influence developers to incorporate accessibility, thus enhancing the user experience in the final product.